Analysis Of Criminal Liability Crime of Legislative Elections (Case Study Legislative Elections in Semarang) - Nur Muchammad; Munsharif Abdul Chalim (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
This study aims to determine the form of criminal responsibility to the crime of legislative elections in Semarang; and obstacles in the implementation of criminal law enforcement against criminal acts of the legislative elections in the city of Semarang.The results showed that the process of law enforcement against criminal acts in general legislative elections held in the context of the criminal justice system in Indonesia, which includes the process of investigation by the police, prosecution by prosecutors and sentencing / verdict by the District Court. Criminal investigations are conducted legislative elections Police, in accordance with the provisions of Article 1 Paragraph (13) of Act No. 2 of 2002 on the Indonesian National Police. In the organization of the legislative elections, in the enforcement of the criminal acts of the legislative elections undergone many obstacles such as: Non-fulfillment of formal requirements and substantive a report criminal election, which resulted election supervisors or investigators difficulty to follow up a report, on terms materially one of them seek witnesses were very hard done by the Election Supervisory; The absence of witnesses because people who know the incident did not dare to testify due to intimidation;The limited time handling criminal offense elections, at both or election supervisory level law enforcement officers.Keywords: Criminal Liability; Crime; Legislative Election.